ANALISIS KOMPARATIF RASIO KEUANGAN PT.ASTRA AGRO LESTARI Tbk, PERIODE 2019-2023 - Ezra Juni Elsa Simanjuntak; Ribka Helena Sidabalok; Eva Sriwiyanti (CV. Denasya Smart Publisher, 2025)
The presentation of financial reports can provide information about the company's assets, liabilities and capital to help investors, creditors and other parties to evaluate the company's financial strengths and weaknesses, liquidity and solvency. The preparation of financial reports must refer to generally accepted accounting principles. This analysis illustrates whether the company's performance is experiencing good growth or not through the method of calculating .financial ratios by comparing financial reports for four periods 2019-2023